Godzilla [videorecording (Blu-Ray)] - Callaham, David, 1977-; Borenstein, Max; Taylor-Johnson, Aaron, 1990-; Watanabe, Ken, 1959-; Olsen, Elizabeth, 1989-; Binoche, Juliette, 1964-; Hawkins, Sally, 1976-; Strathairn, David; Cranston, Bryan, 1956-; Jones, Richard T., 1972-; Adams, CJ, 2000-; Rasuk, Victor, 1984-; et al. (Distributed by Warner Home Video, 2014)
While investigating his mother's death in 1999 at a nuclear power plant, Ford Brody, discovers a conspiracy to hide the fact that giant monsters exist. But it doesn't take long for the world to also find out, as a "Massive Unidentified Terrestrial Organism" attacks Hawaii and Godzilla turns up. Ford, a U.S. Navy officer who works with bomb disposal, helps the military to use warheads to defeat the monsters.